Body mass index in individuals with HIV infection and factors associated with thinness and overweight/obesity - Carolline de Araújo Mariz; Maria de Fátima P. Militão de Albuquerque; Ricardo Arraes de Alencar Ximenes; Heloísa Ramos Lacerda de Melo; Francisco Bandeira; Thaís Gelenske Braga e Oliveira; Érico Higino de Carvalho; Adriana Paula da Silva; Demócrito de Barros Miranda Filho
A cross-sectional study was conducted using body mass index (BMI) to estimate the prevalence of thinness and overweight/obesity and associated factors in 2,018 individuals with HIV/AIDS attending health services referral centers. The dependent variable was classified as thinness, overweight/obesity and eutrophy. Multinomial logistic regression analyses were performed considering eutrophy as the reference level. The prevalence of thinness was 8.8% and of overweight/obesity, 32.1%. The variables associated with thinness were anemia and CD4 cell count < 200mm³. The variables associated with risk of overweight/obesity were age > 40 years and diabetes, and the variables identified as decreasing likelihood of overweight/obesity were having no long-term partner, smoking, presence of an opportunistic disease, anemia, and albumin levels < 3.5mg/dL. The main nutritional problem observed in this population was overweight and obesity, which were much more prevalent than thinness. Older individuals with diabetes should be targeted for nutritional interventions and lifestyle changes.